Parental relational styles: A study with adolescents and their parents - Capano Bosch, Alvaro (2016)
Perceptions of parenting styles by parents and their 12-year-old preadolescents are studied One hundred seven parents and their adolescents enrolled in the first year of secondary education in one of four Catholic schools in Montevideo completed Affection, Rules and Requirements questionnaires. There were significant differences in parent perception in the critical / rejection and inductive factor subscale, depending on the gender of the adolescent. Preadolescent perceptions exhibit significant differences in indulgent and affection scales for father, and in affection, indulgent and inductive scales for mothers. Parents with a primary school education level appear significantly more inductive than those who were areuniversity graduates.